0703 Transvenous Phrenic Nerve Stimulation Provides Safe And Effective Therapy For Cheyne Stokes Respiration. (27th May 2020) - Schwartz, A R; Sundar, K; McKane, S; Germany, R; Khayat, R
Abstract: Introduction: Cheyne-Stokes respiration (CSR), a specific type of central sleep apnea (CSA) is characterized by a waxing and waning pattern of breathing with absent air flow at the ventilatory nadir followed by oxyhemoglobin desaturation. CSR is most common in patients with heart failure (HF) and predicts morbidity/mortality. Therapeutic options remain limited, especially for patients with reduced left ventricular ejection fraction (LVEF). Methods: Patients (n=151) with predominantly CSA were implanted with a transvenous phrenic nerve stimulation device (TPNS, rem edē system, Respicardia Inc.) and randomized to 6-months of active vs. deferred (control) therapy. Patients were divided into subgroups based on percentage of sleep in CSR (<20%, 20-50%, >50%) on their baseline polysomnogram. Response to TPNS, defined by ≥50% reduction in apnea-hypopnea index, and Epworth Sleepiness Scale were assessed. TPNS efficacy and safety was analyzed in each subgroup. Results: As percentage of CSR during sleep increased, more patients had a history of HF and lower LVEF. The proportion of TPNS responders was similar among CSR subgroups at 6 months (63% [17/27] CSR<20%, 52% [11/21] CSR 20-50%, 54% [7/13] CSR>50%); the corresponding control response rates were ≤16% in each subgroup. Central apnea index decreased from median 33, 17 and 30 events/hour in these subgroups to ≤2 in TPNS-treated subgroups; control subgroups had median ≥17 events/hour at 6 months. Daytime sleepiness improved more in TPNS patients with <20% CSR (4/24 points vs. 2 in >20% CSR subgroups). In the CSR>50% subgroup, cardiovascular death (pump failure) was observed in 2/25 control and 0/14 treatment subjects through 6 months. One cardiovascular death (sudden death) occurred in the TPNS 20-50% CSR subgroup. Conclusion: TPNS effectively treats CSA regardless of CSR. Risk of cardiovascular death did not differ by CSR severity with TPNS, but may increase in CSR without treatment. TPNS therapy appears safe and efficacious for CSA with and without CSR. Support: Respicardia and NIH R01 HL 144859